Effect of Packaging on Quality Changes of Black Glutinous Rice (Kham Phayao) Cracker during Storage - Fong-in, Suwalee; Kadwilard, Jenjira; Lainchuea, Saranya; Sanegkham, Siriporn; Dokkham , Wanwisa; Phandaeng, Piya (Burapha Science Journal, 2026)
This study aimed to investigate the effect of packaging on quality changes of black glutinous rice (Kham Phayao) cracker during storage. The black glutinous rice (Kham Phayao) and white glutinous rice in a ratio of 50:50 was used to prepare the rice cracker. Then, the obtained samples were shaped to cracker and were taken to puffing process at 25 0 °C for 5 min. The puffed rice crackers were packed in various packaging pouches: plastic laminated aluminum foil (AF), oriented polypropylene (OPP) and polypropylene (PP) then were kept at 25 °C. The quality of black glutinous rice crackers was estimated at 0, 7, 15, and 30 days. The result depicted that the quality of black glutinous rice crackers tends to be changed when storage time increased. The lightness (L*) and yellowness (b*) values of all treatments were declined, but the value of redness value (a*), aw and moisture content rose in all packaging types. Black glutinous rice cracker packed in the AF bag had the lowest aw and moisture content (p<0.05). Whereas samples were kept in the OPP and PP pouches tend to be higher hardness value than that of the AF pouch (p<0.05). Thiobarbituric acid reactive substance (TBARS) value of products were filled in the AF pouch had significantly lower than those were packed in the OPP and PP pouches (p<0.05). Sensory evaluation was estimated by the quality scoring, the outcome revealed that there were no differences in the sensory quality between sample kept in the different packaging materials (p>0.05) at 15 days. On the other hand, after 30 days, the black glutinous rice crackers contained in the AF pouch were higher intensity score in crispness, taste, and overall acceptability in comparison to the OPP and PP pouches.